(untitled) (Northern International Medical College Journal, 2018)
Background : Amenorrhea means without menstruation. Primary Amenorrhea is the absence of menstruation by 16 years of age in the presence of normal secondary sexual characteristics or by 14 years of age if secondary sexual characteristics have not developed. Objectives : To explore the prevalence of Primary Amenorrhea with etiology in outdoor patient with limited investigation sources Methods : This was a cross sectional study conducted at Rupganj Upazila Health Complex (UHC) from January 2014 to June 2016. During this period total 2500 patients attended at Gynae out patient department (OPD). Among them 45 patients was sorted out with Primary amenorrhea. History and physical examination was done for presence or absence of secondary sexual characteristics, external genital abnormalities. Investigations were ultrasonogram (USG), Hormonal test were Follicle stimulating Hormone (FSH), Lutilizing hormones (LH), Serum Prolactin, Thyroid Stimulating Hormone. Karyotyping done. Data were analysed by using SPSS version 20. Result : In our study prevalence of Primary Amenorrhea was 1.8%. Among them infantile uterus was 17.78%, imperforated hymen was 13.33%. Turner mosaic 11.4%, mullarian agenesis 6.66%, gonadal agenesis-4.45%. hypothyroid 8.89%, hyperprolactenemia-8.89%, and 11.11% patients were with positive progesterone challenge test without anatomical and hormonal abnormalities. Conclusion : Considering the study result, Infantile uterus was the most prevalent etiological factor of amenorrhoea followed by imperforated hymen and Turner mosaic. Northern International Medical College Journal Vol.9(2) Jan 2018: 300-303